ANALYZING ADDRESS TERMS IN GIFTED HANDS: THE BEN CARSON STORY MOVIE SCRIPT: A SOCIOLINGUISTICS PERSPECTIVE - Firdaus, Azura Lu’lu; Laila, Malikatul (Prosiding University Research Colloquium, 2024)
This research is a sociolinguistics research. The aims of this research are to analyze the types of address terms and the social factors that influenced the used of address terms in Gifted Hands: The Ben Carson Story movie script. This research uses manuscript to collect the data. The techniques to collection the data is by documenting through the written movie script and the movie. The theories that applied to identify the types of address terms is by using Wardhaugh (2015) theory, and using Wardhaugh (2006) and Chaika’s (1982) theories to describe the social factors. The result shows that there are 87 datum which consist of 45,97% of first name, 19,54% of kinship term, 16,09% of title plus last name, 10,34% of title only, 4,59% of pet name, and 3,44% of last name. Second, the researcher found 35,63% of family relationship, 28,73% of degree of intimacy, 13,79% of transactional status, 10,34% of occupational hierarchy, 8,04% rank of other, and 2,29% of particular occasion.